On University Freedom in the Canadian Context. - Hare, Kenneth (University of Toronto Press, 1968)
Canadian universities are expanding rapidly and becoming very costly to run and equip. Increasingly the bill is borne by federal and provincial public exchequers. What then should be the proper relationship between government and universities if university freedom is to be preserved? This book discusses the various aspects of the question.
Keywords: Higher education and state -- Canada.; Higher education and state.; Enseignement supérieur -- Politique gouvernementale -- Canada.; Enseignement supérieur -- Politique gouvernementale.; Finance.; EDUCATION.